A study of the effectiveness of training program in Pakaian Saling Erti Sdn. Bhd. based on employees' perceptions / Nur Syahida Rosidi - Rosidi, Nur Syahida (2016)
The purpose of this study is to identify the effectiveness of training program in Pakaian Saling Erti Sdn. Bhd. This study investigates the most use of training techniques either of information distribution technique, simulation technique or on-the-job training technique. The questionnaires had been distributed randomly to the employees in Pakaian Saling Erti Sdn. Bhd. who are Malaysian. The respondents for this study were 70 respondents, but only 59 respondents were selected to be used to find the findings based on Krejcie & Morgan table from a given population. After collected the questionnaires from the respondents, the data had been analyzed by using Statistical Packages for the Social Sciences (SPSS) version 20 to get the results. Based on the findings, most of respondents choose on-the-job training technique as the mostly training program practiced in Pakaian Saling Erti Sdn. Bhd. The findings also show that the level of the effectiveness of training program is good. The researcher suggested that simulation training technique also should be used to train employees by using advance technology besides it can improve the employees' skills and knowledge.